ANALISIS TEMATIK ARTIKEL DALAM JURNAL IFLA EDISI SPECIAL ISSUE: KNOWLEDGE MANAGEMENT AND LIBRARY INNOVATION IN A CHANGING WORLD - Nurislaminingsih, Rizki; Sukaesih, Sukaesih; Komariah, Neneng (BACA: Jurnal Dokumentasi dan Informasi, 2024)
This study aims to map the themes discussed in the articles in the journal. This study is qualitative with theme-based approach. Data collection methods is text documents analysis. The selected documents were analyzed using ATA (Applied Thematic Analysis). The results showed that IFLA Journal Vol. 46, No. 1, March 2020 edition of the Special Issue: Knowledge Management and Library Innovation in a Changing World contains articles with 8 themes, namely library assignments in knowledge management, knowledge management in academic libraries, library restructuring by applying knowledge management principles, knowledge management in college libraries, problems that occur after the implementation of knowledge management, city library networks based on the concept of knowledge management, knowledge sharing activities within institutions, and the weakening of library functions if they do not apply the concept of knowledge management. The conclusion of this study is that the articles published in the journal have the theme of adapting the principles of knowledge management in academic and city library activities along with constraints to alternative solutions. This journal also provides an overview of the problems that will occur if the library has not implemented knowledge management.